Overview of Adherence Diet Management in Type 2 Diabetes Mellitus Patients at Kabila Public Health Center - Nurain Jusuf; Zuhriana K. Yusuf; Sitti Fatimah Arsad (Fakultas Kedokteran Universitas Jenderal Soedirman, 2026)
Diet is a crucial part of managing type 2 diabetes mellitus. One way to achieve this is by following the 3J (Type, Amount, and Schedule) of dietary management. Dietary adherence remains variable, even though patients receive regular education through the PROLANIS program. Dietary non-compliance can result in uncontrolled blood glucose levels and an increased risk of chronic complications. This study aims to describe the 3J diet management compliance in type 2 Diabetes Mellitus patients at the Kabila Community Health Center. This study used a descriptive quantitative design. The research variable was 3J diet management compliance. The population was 289 type 2 DM patients, and a sample of 75 respondents selected using accidental sampling techniques. The instrument used was a 3J diet compliance questionnaire. Data were analyzed univariately using frequency distribution to describe the level of respondent compliance. The results of the study based on indicators, compliance with the type of diet showed that 45 respondents (60.0%) were non-compliant, the number of calories showed that 41 respondents (54.7%) were non-compliant, while the meal schedule showed that 47 respondents (62.7%) were compliant. These findings illustrate that most patients still experience difficulties in managing the type and amount of food, even though they have been quite good at complying with the meal schedule. The Community Health Center is advised to conduct monitoring activities and further research is suggested to develop peer tutoring-based intervention methods.